HUBUNGAN ANTARA MOTIVASI DENGAN HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA KELAS IV DI SD NEGERI 2 CANGKREPLOR - Nurhayati; Rintis Rizkia Pangestika; Suyoto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between motivation and learning outcomes of students at SD Negeri 2 Cangkreplor. The type of research used in this study is quantitative research using the ex-post facto method. The data collection technique in this study in the motivation variable uses a questionnaire, while for the learning outcome variable uses a documentation method in the form of report card scores. Data analysis in inferential statistical analysis is in the form of a correlation test. The results of the study show that there is a relationship between motivation and learning outcomes of students at SD Negeri 2 Cangkreplor from the results of the correlation coefficient calculation (r count) obtained at 0.700 with a positive or unidirectional sign. Then the results of the correlation calculation obtained p-value = 0.00 which means correlation or relationship between two variables at the 0.05 level. This can be seen by comparing r table at the 0.05 level or 5% with the number of samples N = 31, namely 0.355, r count > r table or 0.700 > 0.355 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.